Impact of Dabigatran Treatment on Rotation Thromboelastometry. (28th January 2021) - Sokol, Juraj; Nehaj, Frantisek; Ivankova, Jela; Mokan, Michal; Zolkova, Jana; Lisa, Lenka; Linekova, Ludmila; Mokan, Marian; Stasko, Jan
A rapid and reliable assessment of the dabigatran effect is desirable in dabigatran treated patients with uncontrolled bleeding or before acute surgery. The aim of this study was to study the anticoagulant effects of dabigatran in patients with atrial fibrillation (AF) as assessed by the whole blood assays ROTEM, and how data from these methods correlate to plasma dabigatran concentrations measured by Hemoclot. ROTEM was performed with ROTEM Gamma (Pentapharm GmbH, Munich, Germany). The assays used in our study were Ex-tem and In-tem assay. Plasma dabigatran concentrations were determined by hemoclot thrombin inhibitor assay (Hyphen BioMed, France) at trough and post-dose in 27 patients on dabigatran 150 mg BID. Median plasma dabigatran concentrations at trough were 74 ng/mL (11.2–250) and post-dose (2 h after ingestion) 120 ng/mL (31–282). The ROTEM clotting time (CT) and maximum clot firmnes (MCF) correlated strongly with dabigatran concentrations when activated with the reagents Ex-tem (p < 0.0001) and In-tem (p < 0.0001). In summary, in our study, we have found that the ROTEM variable CT and MCF, when activated with triggers Ex-tem and In-tem, has a strong and highly significant correlation with the plasma dabigatran concentration in a real-life population of AF-patients and could thereby be an alternative to estimate dabigatran concentration in emergency situations. However, additional studies are needed to further validate these findings.